VISUAL IDENTITY OF ENGINEERING GRAPHICS AND INDUSTRIAL DESIGN DEPARTMENT IN UNIVERSITY POLYTECHNICA OF BUCHAREST - CREŢU Ionuţ (Journal of Industrial Design and Engineering Graphics, 2017)
This article aims at drawing a design plan of organizational identity to the Engineering Graphics and Industrial Design Department, University Polytechnica of Bucharest.